What’s in a Label? Articulating Identity through Certification Schemes in Greenlandic Post-Colonial Nation Building - Ren, Carina; Becker Jacobsen, Rikke (Études Inuit Studies, 2023)
In this article, we explore the connection between industrial certification schemes and the articulation of identity within a broader context of Greenlandic independence. As a heuristic tool to explore ethno-political visions and interferences that emerge from the process of national independence, we draw on three sustainability labels used within the Greenlandic fisheries, hunting and tourism sectors. Drawing on their framings of sustainability, we examine whether and in what ways voluntary marked-based certification schemes under the auspices of the Greenland Self-rule Government add to how research has previously defined Greenlandic identities. We further discuss how these certification schemes contain, speak to, support, or contest ethno-national categories with relevance to Greenlandic nation building. In conclusion, we argue that certification regimes in Greenland draw on old as well as emerging categories of collective identity, contributing to the continuous repositioning of Greenland’s key economic sectors in post-colonial nation building.